Extraction of Gold(III) in Hydrochloric Acid Media by 2-Ethyl Hexyl Cyclohexyl Sulfide - Ge, Yunsong; Huang, Zhangjie; Li, Weiqun (Asian Journal of Chemistry, 2014)
A new extractant of 2-ethyl hexyl cyclohexyl sulfide was synthesized and used as an extractant for Au(III) from hydrochloric acid solution. Gold(III) was extracted quantitatively with 2-ethyl hexyl cyclohexyl sulfide in kerosene. Sodium sulfite solution could be used as stripping agent. Extraction parameters of Au(III), including 2-ethyl hexyl cyclohexyl sulfide concentration, contact time of aqueous and organic phases, organic/aqueous (O/A) phase ratio, sodium sulfite concentration and hydrochloric acid concentration of aqueous phase, were studied. Almost all of the Au(III) (> 99 %) was transferred from the aqueous phase into the organic phase. Most of the Au(III) (> 98 %)in the organic phase can be stripped with sodium sulfite aqueous solutions. The proposed method possesses wider range of acidity than the reported methods.